(untitled) (International Journal of Food and Nutritional Sciences, 2023)
This paper studies the issues of digitization saving, problems and challenges. It also discusses the recurring challenges during digitization and its impact on planning and policy. Digitization is the process of converting documents and converting art images into digital images. The concept of saving problems and challenges, including the meaning of digitization, is also explained here. Digitization is a process in which material is converted from hard copy to electronic copies. Key Objectives of Digitization: Increase access to library materials and improve their protection. The process of digitizing library materials has posed many challenges. These challenges include human and technical difficulties, which have consequences for planning and policy. It was concluded that the need to meet the current challenges in modern day libraries and go digital is to provide online services.